Erratum: Li, T., Zhong, G.R., Li, T.H., Deng, W.Q. & Zhang, M. (2024) Amoenoboletus brachysporus (Boletaceae), a new species from Southern China. Phytotaxa 633 (1): 51–59. - Li, Ting; Zhong, Guorui; Li, Taihui; Deng, Wangqiu; Zhang, Ming (Phytotaxa, 2024)
N/A